Changing outpatient referral patterns in a small pediatric nephrology practice - Hanevold, Coral (BMC Pediatr, 2018)
BACKGROUND: We have noted a large number of referrals for abnormal kidney imaging and laboratory tests and postulated that such referrals have increased significantly over time. Understanding changes in referral patterns is helpful in tailoring education and communication between specialists and primary providers. METHODS: We performed a retrospective chart review of new patient referrals to Mary Bridge Children’s Nephrology clinic for early (2002 to 2004) and late (2011 to 2013) cohorts. The overall and individual frequencies of referrals for various indications were compared. RESULTS: The overall number of new visits was similar for early (511) and late (509) cohorts. The frequency of referrals for solitary kidneys and multi-cystic dysplastic kidneys, microalbuminuria and abnormal laboratory results increased significantly (Odds Ratio (OR) and 95% Confidence Interval of OR: 1.920 [1.079, 3.390], 2.862 [1.023, 8.006], 2.006 [1.083, 3.716], respectively) over the time interval while the proportion of referrals for urinary tract infections (UTIs) and vesicoureteral reflux (VUR) decreased by half (OR: 0.472, 95% CI: 0.288, 0.633). Similarly, referrals for urinary tract dilation and hydronephrosis occurred significantly less often (8% versus 6%, OR: 0.737, 95% CI: 0.452, 1.204) with similar changes in referrals for voiding issues (OR: 0.281, 95% CI: 0.137, 0.575). However, these changes were not statistically significant. Frequencies for other indications showed little variation. CONCLUSIONS: Changes in indications for referral likely reflect evolution of practice in management of UTIs and VUR and increased use of imaging and laboratory testing by pediatric providers. These findings have relevance for ongoing education of pediatricians and support the need for collaboration between primary providers and nephrologists to assure the judicious use of resources.